2012
DOI: 10.5194/bg-9-2459-2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil rewetting and thawing on soil gas fluxes: a review of current literature and suggestions for future research

Abstract: Abstract. The rewetting of dry soils and the thawing of frozen soils are short-term, transitional phenomena in terms of hydrology and the thermodynamics of soil systems. The impact of these short-term phenomena on larger scale ecosystem fluxes is increasingly recognized, and a growing number of studies show that these events affect fluxes of soil gases such as carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), ammonia (NH3) and nitric oxide (NO). Global climate models predict that future climati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
305
5
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(341 citation statements)
references
References 266 publications
20
305
5
2
Order By: Relevance
“…These changes decreased CH 4 emissions and increased CO 2 emissions (Gao et al, 2011;Wang et al, 2010). As climate warming continues, the thawing permafrost and subsurface carbon emissions from peatlands will also alter the carbon balance of CH 4 and CO 2 emissions in this region (Dorrepaal et al, 2009;Kim et al, 2012;Knoblauch et al, 2013). In our study, the plots exposed to the combination of soil warming and reduced precipitation showed lower CH 4 emissions.…”
Section: Implications Of Climate Change For Ch 4 Emissions From the Zmentioning
confidence: 66%
See 1 more Smart Citation
“…These changes decreased CH 4 emissions and increased CO 2 emissions (Gao et al, 2011;Wang et al, 2010). As climate warming continues, the thawing permafrost and subsurface carbon emissions from peatlands will also alter the carbon balance of CH 4 and CO 2 emissions in this region (Dorrepaal et al, 2009;Kim et al, 2012;Knoblauch et al, 2013). In our study, the plots exposed to the combination of soil warming and reduced precipitation showed lower CH 4 emissions.…”
Section: Implications Of Climate Change For Ch 4 Emissions From the Zmentioning
confidence: 66%
“…Second, the combination of warming and decreased precipitation can make peatlands drier, accelerating their decomposition and CH 4 oxidation (Dorrepaal et al, 2009;Fenner and Freeman, 2011;Fenner et al, 2001). Third, any climate change that affects substrates, especially dissolved organic carbon export, may influence CH 4 emissions (Chen et al, 2011;Fenner et al, 2007;Kane et al, 2013;Kim et al, 2012;Strack et al, 2008;Worrall and Burt, 2007).…”
Section: Environmental Factors Controlling Ch 4 Emissionsmentioning
confidence: 99%
“…Because microbial nitrification and denitrification, and the subsequent soil-atmosphere N 2 O flux, depend strongly on factors such as soil moisture, temperature, physical characteristics, and N availability (e.g., Potter et al, 1996;Bouwman, 1998;Kim et al, 2012;Bouwman et al, 2013;Butterbach-Bahl et al, 2013;Griffis et al, 2017), N 2 O emissions can exhibit major temporal and spatial variability. For example, Wagner-Riddle et al (2017) found that shortduration freeze-thaw cycles can account for 35-65 % of the annual direct N 2 O emissions from seasonally frozen croplands and that neglecting this contribution would lead to a 17-28 % underestimate of the global N 2 O source (direct + indirect) from agricultural soils.…”
mentioning
confidence: 99%
“…Bu kaynaklar yıl boyunca değişmektedir ve (Atarashi-Andoh et al, 2012) bu değişim genel olarak toprak nemiyle sıcaklığına bağlıdır (Xu and Luo., 2012). Toprak nemi ve sıcaklığı mikrobiyal aktiviteyi etkilemektedir (Kim et al, 2012). Ayrıca toprak solunumu vejetasyon tipine, toprak yönetim pratiklerine, çevre koşullarına ve arazi kullanım tiplerine bağlı olarak değişmektedir (Giardina et al, 2014;Angert et al, 2015).…”
Section: Introductionunclassified